Визначення змін геометричних параметрів крони дерев яблуні при використанні системи мікрозрошення - Бондаренко, Лариса Юріївна; Бондаренко, Лариса Юрьевна; Bondarenko, Larysa; Філіпов, Д. О.; Сушко, Сергій Леонідович; Сушко, Сергей Леонидович; Sushko, Serhii; Дмітрієв, Юрій Олексійович; Дмитриев, Юрий Алексеевич; Dmitriiev, Yurii (My University, 2021)
UK: В статті наведено результати досліджень зміни біометричних показників за віком дерев яблуні. Встановлено, що за літньої вегетації дерев спостерігаються ґрунтові й повітряні посухи та суховії. Тому істотне місце в технології вирощування плодових культур займає зрошення плодових насаджень системами дрібнодисперсного дощування з урахуванням форми крони дерев. В сучасних яблуневих садах найчастіше формують такі крони: вільноростучий кущ, струнке веретено, французька вісь та сплощений кущ. Аналіз динаміки зміни архітектоніки крони дерев для трьох сортів яблуні: Айдаред, Голден Делішес, Ренет Симиренка дозволив встановити, що при спостере-женні зміни площі проекції крони яблуні за віком найбільший вплив має вік, а потім сортові ознаки; при зміні об’єму крони за віком та при зміні площі листової поверхні крони за віком найбільший вплив має вік, потім сорт, а також в окремі роки система формування крони. EN: The article presents the results of research on changes in biometric indicators by age of apple trees. One of the common methods of irrigation, which helps to improve the microclimatic conditions for the growth of fruit trees is fine sprinkling. It has been established that soil and air droughts and dry winds are observed during the summer vegetation of trees. Such meteorological conditions lead to stress of plants in different periods of their growth and development. Therefore, a significant place in the technology of growing fruit crops should be given to irrigation of orchards by fine sprinkling systems. Fine irrigation in many cases can still be combined with fertilization and spraying with pesticides, which is accompanied by a reduction in energy consumption. The analysis of dynamics of change of architecture of a crown of trees for three grades of an apple-tree is carried out: Idared, Golden Delicious, Renet Simirenko. It is established that when observing the dynamics of the projection area of the apple crown by age in four different systems of crown formation, the change in the projection area is most influenced by age, and then varietal characteristics. Analyzing the changes in the volume of the crown by age in three varieties, it was found that the change in volume is most influenced by age, then the variety. The deviation from the gradual change of the projection area and the volume of the crown in some years is due to the influence of environmental conditions and the sensitivity of trees to this influence. Studies of changes in the leaf surface area of the crown with age have shown that the change in leaf surface area is most influenced by age, then the variety, and also in some years the system of crown formation. RU: В статье приведены результаты исследований изменения биометрических показателей в зависимости от возраста деревьев яблони. Установлено, что при летней вегетации деревьев наблюдаются грунтовые и воздушные засухи и суховеи. Поэтому существенное место в технологии выращивания плодовых культур занимает орошение насаждений системами мелкодисперсного дождевания с учетом формы кроны деревьев. В современных яблоневых садах чаще всего формируют такие кроны: свободно растущий куст, стройное веретено, французская ось и сплющенный куст. Анализ динамики изменения архитектоники кроны деревьев для трех сортов яблони: Айдаред, Голден Делишес, Ренет Симиренко позволил установить, что при наблюдении изменения площади проекции кроны яблони по возрасту наибольшее влияние оказывает возраст, а затем сортовые признаки; при изменении объема кроны по возрасту и при изменении площади листовой поверхности кроны по возрасту наибольшее влияние имеет возраст, затем сорт, а также в отдельные годы система формирования кроны.
Determination of changes in geometric parameters of apple tree crowns using a micro-irrigation system
Определение изменений геометрических параметров кроны деревьев яблони при использовании системы микроорошения
Keywords: дрібнодисперсне дощування; плодові культури; крона дерева; графіки залежності; сортові ознаки; fine sprinkling; fruit crops; tree crown; graphics of dependences; varietal characteristics; мелкодисперсное дождевание; плодовые культуры; крона дерева; графики зависимости; сортовые признаки